2022
DOI: 10.1111/jam.15706
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Streptococcus agalactiae sialic acid mutant and evaluation of its potential as a live attenuated vaccine in Nile tilapia (Oreochromis niloticus)

Abstract: Aims: This study aimed to develop a live attenuated vaccine as an effective approach to prevent streptococcosis in tilapia (Oreochromis niloticus). Methods and results:We eliminated the virulence factor, sialic acid (Sia) encoded by the neuA-D gene cluster from the Group B Streptococcus (Streptococcus agalactiae, GBS) strain WC1535, to construct Sia-deficient S. agalactiae (ΔSia) mutant by homologous recombination. Results showed that the ΔSia mutant had higher adherence to HEp-2 cells and lower resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…FKV was prepared with 0.3% formalin from WC1535. Our previous work showed that LAV ∆Sia, a gene-deleted strain of WC1535 obtained through homologous recombination, confers protection against homologous infection in tilapia (Hao et al, 2022).…”
Section: Strainsmentioning
confidence: 99%
See 3 more Smart Citations
“…FKV was prepared with 0.3% formalin from WC1535. Our previous work showed that LAV ∆Sia, a gene-deleted strain of WC1535 obtained through homologous recombination, confers protection against homologous infection in tilapia (Hao et al, 2022).…”
Section: Strainsmentioning
confidence: 99%
“…In addition, 100 μL of the mixture was cultured on BHI plates for 48 h to determine if the bacteria were still viable. Similarly, LAV ΔSia (Hao et al, 2022) was prepared by being streaked onto BHI agar, cultured, harvested, and adjusted to the final concentration of 2.0 × 10 9 CFU mL −1 .…”
Section: Vaccine Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…GBS is a causal agent of tilapia streptococcosis, which has caused serious economic losses (Laith et al, 2017;Zhang et al, 2017;. Studies have shown that the formalin-killed vaccine (FKV) of GBS protected tilapia against GBS infection for up to 180 days (Pasnik et al, 2005), and our previous work demonstrated that in tilapia, a live attenuated vaccine (LAV ∆Sia) conferred protection against homologous GBS infection (Hao et al, 2022). Although considerable research has been conducted on vaccines for tilapia against GBS infection, a systematic comparison of the effects of FKV and LAV on the hindgut mucosal flora and immune response of tilapia has received little attention.…”
Section: Introductionmentioning
confidence: 97%